1 Peter - Doriani, Daniel M., 1953- (Phillipsburg, New Jersey : P & R Publishing, 2014)
Many Christians around the world today face severe persecution, while others daily feel the weight of cultural pressure against them. The apostle Peter speaks to this as he reminds us that Christians are aliens and exiles in an often hostile empire. Yet we are simultaneously the chosen of God, equipped by Jesus work for us and in us to live faithfully in our dual identity. In this exposition of 1 Peter, Daniel Doriani explains how the work of Christ enables Christians to live with hope, joy, and faithfulness in a pagan world. He also explores Peters emphasis on the kind of life that pleases God - a life that includes respect for authorities, just or unjust; godly behavior as a wife, husband, or elder; and, by God's grace, good deeds, courage, and a firm stand in the face of trials. As are all the books in the Reformed Expository Commentary series, this exposition of 1 Peter is accessible to both pastors and lay readers. Each volume in the series provides exposition that gives careful attention to the biblical text, is doctrinally Reformed, focuses on Christ through the lens of redemptive history, and applies the Bible to our contemporary setting.--Publisher
Strangers in a strange land (1 Peter 1:1-2) -- A sure and living hope (1 Peter 1 :3-9) -- The authority of Peter and his epistle (1 Peter 1:10-12) -- Hope and holiness (1 Peter 1:13-21) -- Gospel purification (1 Peter 1:22-2:3) -- Christian identity (1 Peter 2:4-10) -- Pilgrims and citizens (1 Peter 2:11-17) -- A life shaped by the crucified Christ (1 Peter 2:18-25) -- Beautiful wives, considerate husbands (1 Peter 3:1-7) -- The good life, the peacable kingdom (1 Peter 3:8-12) -- The right fear (1 Peter 3:13-18) -- The work of the living Christ (1 Peter 3:18-22) -- Breaking with sin (1 Peter 4:1-6) -- Gifts from God, gifts for God (1 Peter 4:7-11) -- God's way to endure trials (1 Peter 4:12-19) -- Jesus shepherds his church through servant leaders (1 Peter 5:1-4) -- Humble yourselves (1 Peter 5:5-6) -- Counsel and blessing (1 Peter 5:7-14).
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries